PENUMBUHAN KEDISIPLINAN SEBAGAI PEMBENTUKAN KARAKTER PESERTA DIDIK DI MADRASAH - Fatah Yasin (Fak. Tarbiyah UIN Maliki Malang, 2011)
Discipline is a condition that is created through a training process developed into a series of behaviors in which there are elements of obedience, obedience, loyalty, order and it was all done as a responsibility that aims to introspective. Discipline can be influenced by two factors yatu, internal factors (innate factors, awareness, interest, motivation and mindset) and external factors (example, advice, training, environment, and group).While efforts can be done to foster habituation or discipline to do exercise, give an example, provide insight, and control. Thus the discipline that is formed will be a character on students.